ANALISIS EFEKTIVITAS KINERJA LALU LINTAS SESUDAH ADANYA FLYOVER AHMAD YANI (SEMARANG) - Dede Yusuf Permadi; Shafa Tasya Sutopo; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
Semarang City is the capital city of Central Java Province, Indonesia as well as the fifth largest metropolitan city in Indonesia after Jakarta, Surabaya, Medan and Bandung. As one of the most developed cities on the island of Java, Semarang City has a population of 1.68 million people. Semarang Ahmad Yani Airport is the most important airport in Central Java. The existence of the airport in the city of Semarang is quite strategic because it is supported by the high intensity of socio- economic activities. Ahmad Yani Airport itself is part of a series of activities in Central Java. As a service-based city, the city of Semarang certainly requires an airport that is able to connect not only national but also international points. The aim of this research is to analyze the conflict points of congestion at the study site after the construction of the Ahmad Yani Airport Flyover and compare the degree of saturation (S) before and after the construction of the Ahmad Yani Airport Flyover. This study is used the 1997 Indonesian Road Capacity Manual (MKJI) method. Results of the analysis concluse degree of saturation 0.16 < 0.19 for the Puri Anjasmoro road section, and 0.19 < 0.28 for the Anjasmoro Raya road section. Meanwhile, the degree of saturation for the Ahmad Yani Airport Flyover Road section, Semarang is 0.10.